Grupoterapia e Suporte emocional em Cuidados Paliativos: possibilidades de intervenção no diagnóstico do cancro de mama metastático - Tatiane Cristine de Souza Lima (2024)
The diagnosis of metastatic breast cancer (MBC) represents a profound transformation in a woman's life, generating intense emotional suffering. Palliative care interventions focus on improving quality of life and relieving suffering. Thus, this paper explores group therapy as an effective alternative for managing and providing emotional support to these patients. The central objective was to analyze existing studies on the effects of group psychotherapy in alleviating emotional distress in MBC cases. The methodology employed was an integrative review with the guiding question: "Is group psychotherapy a viable and accessible psychological strategy for addressing the challenges and limitations imposed by metastatic breast cancer?" Data collection was conducted through electronic databases such as PubMed, SciELO, PsycINFO, Scopus, and Lilacs, between January and August 2024, including publications from the last decade. Of the 87 articles found, only 03 were selected based on inclusion and exclusion criteria. It was concluded that group psychotherapy shows positive results in improving quality of life by providing information, reducing social isolation due to peer connections, minimizing anxiety and depressive symptoms, and creating a safe space for emotional expression and sensitive topics. Therefore, therapeutic groups are a valuable strategy in palliative care, promoting well-being and resilience in patients with metastatic breast cancer.